APPLICATION OF ASSOCIATION RULE MINING AND MINING SEQUENTIAL PATTERNS ON CRM PT. ARMADA INTERNATIONAL MOTOR - Nina Setiyawati (CCIT Journal, 2018)
Keeping in touch with customers is a step that must be done by the company to increase customer loyalty. CRM is a set of processes to acquire, maintain and enhance the values ​​for customer satisfaction for the continued growth of corporate profits. With data mining for extracting knowledge, performance can be improved CRM in obtaining information about customers. In this study, carried out by the application of CRM design Association rule mining and sequential pattern mining techniques to provide recommendations to the customer service type PT Armada International Motor. CRM is built based mobile and able to provide effective services and recommendations for customers